The Ubiquitin Code of NODs Signaling Pathways in Health and Disease - Martínez-Torres, Rubén Julio; Chamaillard, Mathias (Frontiers in Immunology, 2019)
NOD1 and NOD2 belong to the family of intracellular Nod-like receptors (NLRs) that are involved in maintenance of tissue homeostasis and host defense against bacteria and some viruses. When sensing such microbes, those NLRs act as hitherto scaffolding proteins for activating multiple downstream inflammatory signaling pathways to promote the production of cytokines and chemokines that are ultimately important for pathogen clearance. In recent years, substantial advances have been made on our understanding of a contextual series of intracellular processes that regulate such group of innate immune molecules, including phosphorylation and ubiquitination. Specifically, we will herein discuss those recently described post-translational modifications of either NOD1 or NOD2 that fundamentally contribute to the robustness of protective responses within specific tissues through either internal domain association or external interactions with various proteins. From a public health perspective, it is then anticipated that a better understanding how genetic mutations and deregulation of these activating and repressing mechanisms might break down in diseases would open up new therapeutic avenues for humanity.